Legal Effort of the Prosecutor's Office Against the Pre-trial Decision Ordering the Immediate Transfer of the Case to Trial (Case Study of Decision Number 3/Pid.Pra/2018/PN Pso) - GM, I Gusti Ngurah Bagus Girindra; Triyanto, Toni (KnE Social Sciences, 2025)
Decision number 3/Pid.Pra/2018/PN Pso is a pretrial decision that has permanent legal force because no appeal or cassation can be made, with the following verdict in essence: Declaring the Instruction Letter (P-19) invalid and not binding; declaring the action that stops the prosecution is invalid; ordering the case files to be immediately transferred to the Poso District Court for trial. This thesis aims to study and analyze the authority of the Pretrial Judge in examining and deciding cases regarding the invalidity of the termination of the investigation and the invalidity of the termination of the prosecution based on the Notification Letter of Progress of the Investigation Results; the authority of the Pretrial Judge in ordering the Prosecutor’s Office to immediately transfer the case to trial; legal efforts that can be taken by the Prosecutor’s Office against the verdict ordering the Prosecutor’s Office to immediately transfer the case to trial. It uses a normative juridical method, theory of authority, theory of law enforcement, and theory of criminal justice system. The results of the study show that the Pretrial Judge has exceeded his authority and there has been a judicial error or a clear error in trying the object of the pretrial because the basis for submitting the pretrial application is the Notification Letter of Progress of Investigation Results and there has been no Letter of Termination either at the Investigation or Prosecution level. The Pretrial Judge has exceeded his authority and there has been a judicial error or a clear error in examining and deciding the case to immediately transfer the case files or continue the prosecution of the case to the trial because the one who can determine whether or not a prosecution of a case can be carried out is the Public Prosecutor as dominus litis.